W poszukiwaniu zależności między przedsiębiorczością a efektywnością polskich organizacji - Dyduch, Wojciech (In Search of the Relation between Corporate Entrepreneurship and Performance, 2006)
The primary challenge of this research was to determine the relation between corporate entrepreneurship measured with different scales, and performance of the organisations in transition economy. In my work I compare various contemporary approaches towards analysing firm's entrepreneurship: ite concept of entrepreneurship as opportunity-based management [Stevenson, Jarillo 1990], and entrepreneurial orientation [Lumpkin, Dess 1996]. I analyse which dimensions of entrepreneurship correlate best with performance in order to build an integrated tool for measuring corporate entrepreneurship.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 281-287